2017
DOI: 10.1038/srep39604
|View full text |Cite
|
Sign up to set email alerts
|

Serelaxin treatment reverses vascular dysfunction and left ventricular hypertrophy in a mouse model of Type 1 diabetes

Abstract: Serelaxin prevents endothelial dysfunction in the mouse aorta ex vivo and inhibits apoptosis in cardiomyocytes under acute hyperglycaemia. Less is known about the effects of serelaxin in an in vivo mouse model of diabetes. Therefore, we tested the hypothesis in streptozotocin (STZ)-treated mice that serelaxin is able to reverse diabetes-induced vascular dysfunction and cardiac remodelling. Mice were divided into citrate buffer + placebo, STZ + placebo and STZ + serelaxin (0.5 mg/kg/d, 2 weeks) groups. After 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
39
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 50 publications
7
39
1
Order By: Relevance
“…In accordance with previous studies 23 , mice suffering from type 1 diabetes mellitus displayed increases in blood glucose levels at 6w, 9w, and 12w after STZ application versus corresponding controls, respectively (Fig. 1a).…”
Section: Stz-induced Type 1 Diabetes Mellitus Is Associated With Impasupporting
confidence: 92%
See 1 more Smart Citation
“…In accordance with previous studies 23 , mice suffering from type 1 diabetes mellitus displayed increases in blood glucose levels at 6w, 9w, and 12w after STZ application versus corresponding controls, respectively (Fig. 1a).…”
Section: Stz-induced Type 1 Diabetes Mellitus Is Associated With Impasupporting
confidence: 92%
“…Interestingly, we observed less collagen I at 12w post-STZ compared to 9w STZ, paralleled by lower Lox and LoxL2 levels, as markers for collagen cross-linking 36 . The reduction in collagen at 12w STZ www.nature.com/scientificreports www.nature.com/scientificreports/ per se is contradictory to already published studies, reporting higher collagen levels 3,23,31 . Only one study, investigating the effect of thioredoxin-interacting protein, reported less myocardial collagen at 16w STZ compared to controls 37 .…”
Section: Discussioncontrasting
confidence: 80%
“…However, NO-mediated vascular relaxation was damaged in insulin resistance and diabetes, suggesting endothelium dysfunction [29]. Furthermore, endothelial cell injury and dysfunction are associated with upregulation of oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…However, none of these assay methods have published details regarding sensitivity and reliability. Nevertheless, some of them have been successfully used for clinical studies with different questions, e.g., birthweight regulation and other pregnancy complications (17,18,30), peripartum cardiomyopathy (31), vascular dysfunction in type 1 diabetes (32), and cirrhosis (33).…”
Section: Discussionmentioning
confidence: 99%